Estimativa de estados e parâmetros para microtrocadores de calor utilizando filtros de partículas - Cosmo, Marcos Palácio (2016)
The control of the temperature field in photovoltaic cells has fundamental importance for its correct functioning. This work deals with the analysis through inverse problems involving two Micro-heat exchanger composed respectively of one and three circular microchannels. These equipments are commonly used in the temperature control of photovoltaic cells, its efficiency is directly associated with the flow velocities inside the microchannels that make up the Micro-heat. In this work, estimates were obtained for the flow velocities of the fluid inside the microchannels and, also, for the entire temperature field of the Micro-heat exchanger. The solution of the associated direct problem was obtained through Fluent software (ANSYS) that was interconnected to the MatLab platform. The MatLab was used in the implementation of the SIR Filter, on the inverse problem. The results obtained by simulated measurements of temperature showed that the fluid velocities and the temperature range of the Micro-heat exchanger can be estimated accurately in the presence of different noise levels in the measurements.